In Situ Growth of Zeolitic Imidazolate Frameworks Nanocrystals on Ordered Macroporous Carbon for Hydroquinone and Catechol Simultaneous Determination. Issue 6 (19th March 2020) - Tang, Jing; Liu, Renhao; Li, Jie; Hui, Zhenzhen; Zheng, Shengbiao; Wu, Jiwei; Guo, Jiahao; Wang, Xuchun; Wang, Jianfei
Abstract : A Co-containing zeolitic imidazolate framework (ZIF-67) and ordered macroporous carbon (OMC) composite has been made via in situ growing ZIF-67 in the suspension of OMC. Different sizes of ZIF67-OMC-x (400, 700, 1000 nm) hybrid composites were synthesis by adding different amount of polyvinyl pyrrolidone (PVP). The SEM and TEM images demonstrated that the sizes of ZIF-67 matched well with the macropores of the OMC matrix in as-prepared ZIF67-OMC-400 nm composites. The intriguing structure of ZIF67-OMC-400 hybrid composites utilized synergistic interactions between the large surface area and ordered porosity structure of ZIF-67 and the high conductivity of OMC. More importantly, ZIF67-OMC-400 was explored as a novel modifying material for fabricating electrochemical sensor and then was utilized successfully for catechol (CC) and hydroquinone (HQ) simultaneous detection. Under the optimized condition, wide linear responses of this sensor were obtained for HQ and CC detection in the range of 0.1 μ M to 100 μ M. The modified electrode was successfully demonstrated for real samples such as river water with satisfactory results.